Effect of 4-Week Protocol of Kegel Exercise on Pelvic Floor Strength on a Patient with Ovarian Endometriosis—A Case Report - Manali Dey (International Journal of Women's Health Nursing And Practices, 2025)
Purpose: The purpose of this case study was to describe the effects of Kegel exercise in a 4-week protocol for a patient with endometriosis associated with urinary incontinence. Case description: A 23-year-old female patient presented with chronic low back pain and also complained of difficulty in holding urine and leakage while doing forceful activities like lifting heavy objects, coughing, and sneezing in the past 6 months. She also complained of pain in her lower abdomen, which aggravated during menstruation along with menorrhagia. She had a past medical history of 1 cesarean section and 2 miscarriages. The patient was diagnosed with endometriosis associated with urinary incontinence by the concerned gynecologist. Plan of care: Upon assessment, the patient’s pelvic floor muscle strength was found to be 1 and severity of urinary incontinence was 5. Interventions included Kegel exercises modified in different positions for a total of 4 weeks. Outcome measures included were Modified Oxford Grading for testing pelvic floor muscles strength and Sandvic Severity Index for urinary incontinence. Outcomes: The data was collected pre and post treatment and were computed using SPSS software. It was seen that strength of pelvic floor muscles increased from 1 to 2 after 4 weeks of intervention and the severity score of urinary incontinence decreased from 5 to 3. Wilcoxon signed rank test was done and p value = 0.0023 for pelvic floor muscle strength and p = 0.001 for urinary incontinence, which is found to be clinically significant (p Conclusion: Following 4 weeks of home exercise program, the patient demonstrated increase in the pelvic floor muscle strength and decrease in the severity of urinary incontinence.
Keywords: Kegel exercise; endometriosis; pelvic floor muscle (PFM); urinary incontinence